Behavioral Tests to Assess Short- and Long-Lasting Sensorimotor Deficits Following Transient Focal Cerebral Ischemia in Rodents - Wong-Guerra, M (Springer Science and Business Media Deutschland GmbH, 2025)
Cerebrovascular diseases are highly lethal and disabling events. Stroke is most commonly modeled using focal ischemia, of which middle cerebral artery occlusion (MCAO) is widely employed. Reproducible and reliable animal models are crucial for studying the pathophysiology of diseases and the evaluation of therapeutic candidates. However, despite showing efficacy in experimental studies, neuroprotective approaches have failed to translate into clinical benefit so far. A key measure to improve preclinical stroke research is the inclusion of functional endpoints intended to cover a wide range of parameters. The selection of appropriate tests is a critical issue and a challenging task, given the many variables to be considered. These variables include the experimental species, strain, sex, age, occlusion method and duration, infarct size and location, and degree of collateral irrigation, operational costs, among others. The focus of this review is on the behavioral tests most commonly used to identify neurological alterations associated with sensorimotor deficits following transient cerebral ischemia in rats and mice. Commonly used tests include the neurological score, the adhesive removal test, the hanging wire test, the corner test, the cylinder test, and the rotarod test. Functional endpoints must be included in preclinical testing, including sensorimotor and cognitive function, given the variable recovery rates of specific neurological functions. Importantly, screening for sensorimotor function prior to cognitive testing ensures accurate conclusions and helps identify the best specific conditions with minimal confounding by neurological abnormalities. Behavioral outcomes allow assessment of the severity, persistence, or recovery of post-ischemic injury over time. © The Author(s) under exclusive licence to Maj Institute of Pharmacology Polish Academy of Sciences 2025.